The Role of Legal Analysis and Evaluation in Realizing the Formation of Better Legislation - Joko Sriwidodo; Ramlani Lina Sinaulan (KRTHA BHAYANGKARA, 2025)
Evaluation of legal rules will produce recommendations on whether the rules need to be changed, revoked, or maintained. This process is part of the ex-post legal analysis method carried out on legal rules that have been enacted in accordance with Article 7 of the PPP Law , including Laws/Government Regulations in Lieu of Laws, Government Regulations, Presidential Regulations, Provincial Regulations, Regency/City Regulations, and other types of legal rules as stipulated in Article 8 paragraph (1) of the PPP Law . In legal analysis and evaluation, several methods are used with steps to inventory data on regulations related to the issues that have been determined, including colonial regime regulations that are still in effect today. Related supporting data is also needed to complete the material. Analysis and evaluation of related regulations are deepened by using the supporting data for further refinement. Based on Results Report Analysis And Evaluation Law related order manage government by Body Coaching Law National (BPHN) Ministry Law and human rights in 2020 , there are a number of The law that was carried out analysis And evaluation , including : Law Number 15 of 2006 concerning the Audit Board, Law Number 15 of 2004 concerning the audit of state financial management and accountability, Law Number 37 of 2008 concerning the Ombudsman, Law Number 25 of 2009 concerning Public Services, Law Number 5 of 2014 concerning State Civil Apparatus, Law Number 30 of 2014 concerning Government Administration and several others.